Technology Addiction in Children - Hilčenko, Slavoljub; Jakovljević, Nebojša (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2019)
ncontrolled and inappropriate use of technology (mobile phones, tablets and PC) among pre-school children is harmfulto their physical and mental development. The use of technology at this age should not be limited to 30 minutesper day.Anything over that timecan cause addiction.Even during this interval,the use of inappropriate content i.e., games, social networks may not encourage deepanalytical thinking; instead,it makes a ‘flow water heater’ from a brain causingthe reception of a huge amount of information that cannot be processed or stimulated by the brain to solve problems and develop synapses that are responsible for functional thinking.On the other hand, during that period, children experience a range of emotions such as sadness, anger, happiness, fear, love, surprise, disgust, and shame.These emotions cause an increasein serotonin levels, which functions as a form of morphine in children’s brain. It is much more effective for a child to engage in some form of motor activitiese.g., playing, climbing or crawling which successfully stimulates the formation of synapses in the child's brain. This new generation of children addictedto technology in schools creates problems. The aim of this paper is to outlinethis multifacated problem.